2021
DOI: 10.4028/www.scientific.net/ddf.410.405
|View full text |Cite
|
Sign up to set email alerts
|

Refining of Primary Aluminum from Vanadium

Abstract: The paper investigates the technology of refining primary aluminum from vanadium impurities, based on flux treatment with boron-containing fluxes. In the Pavlodar region of the Republic of Kazakhstan, on the basis of local enterprises, the production of primary aluminum and products based on local raw materials is developing. The main problem in the production of primary aluminum on the basis of JSC “Kazakhstan Electrolysis Plant” is the presence of undesirable vanadium impurities, which pass into metal during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…preliminary processing of filter grains for cleaning from aluminum scrap (Figure 1), including grinding of granules in a drum mill and classification of the metal and non-metal parts of the processed material; Figure 1 -General view of used filters metallurgical processing of separated aluminum scrap by remelting in an induction crucible furnace and refining using complex technology described by the authors in [5];…”
Section: Methodsmentioning
confidence: 99%
“…preliminary processing of filter grains for cleaning from aluminum scrap (Figure 1), including grinding of granules in a drum mill and classification of the metal and non-metal parts of the processed material; Figure 1 -General view of used filters metallurgical processing of separated aluminum scrap by remelting in an induction crucible furnace and refining using complex technology described by the authors in [5];…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this work is to study the physicochemical properties of Al-B ligatures with different boron content -1.08%, 2.77% and 4.5%. It was found that a large amount of B in the master alloy, with accelerated cooling, which has a narrower crystallization range with a lower temperature, contributes to the refinement of the internal structure of the grain throughout the section [23].…”
Section: Experimental Studymentioning
confidence: 99%
“…Many technologies for processing wastes from alumina production are expensive for the implementation of the presented studies, and most of them are accompanied by complexity and multi-stage processing processes. According to its composition, bauxite waste can be used in various industries [ [3], [4], [5], [6], [7]].…”
Section: Introductionmentioning
confidence: 99%